Role of the Multidisciplinary Team (MDT) Meetings in Rectal Cancer Management - Ajith John; Rohin Mittal (Journal of Gastrointestinal and Abdominal Radiology, 2025)
The management of rectal cancer is complex and requires the expertise of multiple disciplines and various treatment modalities. Multidisciplinary team (MDT) discussions are essential for the optimal management of patients with rectal cancer.